2023
DOI: 10.3389/fgene.2023.1181240
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge of and attitudes toward genetics and genetic testing in Brunei Darussalam

Abstract: The world has been experiencing encouraging research in genetics, but current public knowledge, awareness, and perception of this area remain unknown for Brunei Darussalam. This study aimed to investigate the Brunei population’s genetics and genetic testing literacy, and their attitude toward them. A cross-sectional study was carried out targeting public population in Brunei Darussalam. Questionnaires on knowledge and attitudes were randomly distributed in frequented venues in the Brunei–Muara district and upl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…This finding is consistent with [ 17 ] who reported that less than half of the respondents expressed interest in genetic testing to prevent specific diseases such as cancer, cardiovascular disease, diabetes, or dementia. However, there is a discrepancy with the study by Jaya et al [ 11 ] where the majority of participants demonstrated a positive attitude toward genetic services. Additionally, Vermeulen et al [ 16 ] found that 76.9% of participants were willing to undergo a genetic test if their relatives had a genetic disease.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…This finding is consistent with [ 17 ] who reported that less than half of the respondents expressed interest in genetic testing to prevent specific diseases such as cancer, cardiovascular disease, diabetes, or dementia. However, there is a discrepancy with the study by Jaya et al [ 11 ] where the majority of participants demonstrated a positive attitude toward genetic services. Additionally, Vermeulen et al [ 16 ] found that 76.9% of participants were willing to undergo a genetic test if their relatives had a genetic disease.…”
Section: Discussioncontrasting
confidence: 77%
“…Comprising eight items on a scale of 1 to 3, responses ranged from agreement to disagreement. The items were rephrased from previous studies [11][12][13] with some modifications. The total attitude score ranged from 1 to 24, and respondents scoring 60% or above were considered to have a positive attitude toward genetic testing.…”
Section: Data Collection Toolsmentioning
confidence: 99%